(untitled) (New Delhi, 2008)
Preservation is concerned with problems such as repair, dusting, fumigation, deacidification, air-conditioning, lamination, binding, storage, etc. The principles of preservation of documentary materials in libraries, archives, and digital databases in the light of rapid technological advances need to be reexamined and reevaluated. This book consists of 33 papers written by scholars, experts, and practicing librarians. These contributors discuss various preservation problems experienced in their work environments, and they offer practical solutions.
Keywords: Archival materials,Library materials,Digital preservation.,Tài liệu lưu trữ,Tài liệu thư viện,Bảo quản tài liệu số; Conservation and restoration.,Conservation and restoration.,Bảo tồn bảo quản,Bảo tồn bảo quản